Ansatte og temaet seksualitet: Hvilke utfordringer opplever ansatte i sitt arbeid når det gjelder voksne med intellektuell funksjonsnedsettelse og seksualitet? - Hilde Lunde (Nordisk Tidsskrift for Helseforskning, 2014)
Caregivers awareness of sexuality This study deals with the results from two focus group interviews with 13 students from education in "Sexology and Disability" by Oslo and Akershus University College (HIOA). The purpose of this study was to highlight the experiences and perceptions of employees in their work with the theme of sexuality. Findings from the study show that it is still difficult to talk openly about people with developmental disabilities and their sexuality. Many see it as a taboo area. The study shows that both the caregiver and care recipient are in need of training. Staff working with the theme of sexuality may feel stigmatized by colleagues. They get little support from managers and colleagues. Management must ensure good care for the client. The study indicates that employees should have knowledge and methods to meet the challenges of sexual education and prevent abuse.